Probing Molecular‐Transport Properties using the Superconducting Proximity Effect. Issue 3 (12th January 2017) - Katzir, Eran; Sukenik, Nir; Kalcheim, Yoav; Alpern, Hen; Yochelis, Shira; Berlin, Yuri A.; Ratner, Mark A.; Millo, Oded; Paltiel, Yossi
Abstract : Molecular electronics research focuses on the study and application of molecular building blocks for the fabrication of nanoscale electronic devices, and on utilizing their self‐organization properties to achieve large‐scale electronic circuits. One of the key issues in molecular electronics is to identify the mechanism governing the electrical conductivity along the molecules. More specifically, the problem is to determine whether the junction behaves as a tunnel barrier, or the junction provides electron or hole conduction channels through the molecule. Due to the large energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), it is usually assumed in calculations that the molecule may contain only one conducting channel either for electrons or for holes. Experimentally, measurements using a local‐probe tip or a small gap between two metallic leads strongly depend on the nature of the linkage between the molecules and the contacts, which is hard to optimize. Here, a new approach is presented to study the electronic and transport properties of molecules using the superconducting proximity effect. Insight into these properties is gained by monitoring the modifications of the superconducting properties upon linking nanoparticles to a superconductor via the studied molecules. Abstract : Molecular electronics research focuses on the study and application of molecular building blocks for realizing nanoscale electronic devices. One key issue is to identify the electrical‐conductivity mechanisms in molecules. The use of the superconducting proximity effect as a simple probe for molecular transport properties is reviewed and a new approach is presented to study the electronic and transport properties of molecules using the superconducting proximity effect.